Potention of L-carnitine supplementation on changes in ejection fraction and left ventricular dimension in case of dilatative cardiomyopathy in children - Wahyu Wibowo, - (Foundation for Enviromental Protection and Research, 2020)
Background: Cardiomyopathy is a rare cardiac muscle disease with poor prognosis and high mortality. The main goal of dilated cardiomyopathy therapy is to restore and maximize cardiac function, but to date no medication has met these criteria. The use of oral L-carnitine as a dilated cardiomyopathy therapy has a potency to gives good results in restore and maximize cardiac function. Purpose: Knowing the effect of L-carnitine supplementation in children with cardiomyopathy on ejection fraction and left ventricular dimensions. Method: Experimental studies with randomized control trial design were conducted for one year, to determine the effect of L-carnitine in the experiment by performing twice the ejection fraction measurements and left ventricular dimensions performed before and after the administration of L-carnitine for 1 month. This research does not use blind method. Sampling was done randomly with comparison control. Different test was conducted with Saphiro-Wilk followed by T-test. Result: Fourteen samples were analyzed. In the treatment group, an increase in ejection fraction (p = 0.033), decreased left ventricular systolic phase end dimension (p = 0.043) and at the end of diastolic phase (p = 0.170). There was a significant difference in the increase of ejection fraction between treatment group and control group (p = 0,035), but no significant difference was found between treatment group and control group of final phase of systole (p = 0,228) and final phase of diastol (p = 0,704). Conclusion: L-carnitine supplementation in children with dilatative cardiomyopathy can increase ejection fraction, but not decrease the left ventricular dimension.